1959
DOI: 10.1152/ajplegacy.1959.197.4.915
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic influences on circulation of the gastric mucosa of the rat

Abstract: A method is presented for quantitatively evaluating the gastric mucosal blood content in rats by densitometric measurement of the India ink content of the mucosa following the intra-aortic injection of India ink in the living animal. Animals injected after laparotomy alone showed a very sparse accumulation of India ink in the mucosa. Interruption of the sympathetic nerve supply to the stomach by splanchnic anesthesia or splanchnic section produced a marked filling of the mucosal capillary bed. The mucosal capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
1995
1995

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been reported that gastric mucosal blood flow (GMBF) significantly decreases in almost all portions of the stomach at the active stage of ulcer formation [10,11], just after the development of gastric ulcers [12], and returns to the same level as normal con trols at the healing and scarring stages [3,13]. Thus, GMBF was thought to be one of the most important defensive factors in the devel opment of gastric injuries.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that gastric mucosal blood flow (GMBF) significantly decreases in almost all portions of the stomach at the active stage of ulcer formation [10,11], just after the development of gastric ulcers [12], and returns to the same level as normal con trols at the healing and scarring stages [3,13]. Thus, GMBF was thought to be one of the most important defensive factors in the devel opment of gastric injuries.…”
Section: Discussionmentioning
confidence: 99%